Digital Public Service Quality (PS-DigQual): Proposal of a Multidimensional Framework - Alves, Juliano Nunes; Battistella, Luciana Flores; Lehnhart, Eliete dos Reis; Vieira, Kelmara Mendes; Zonatto, Vinícius Costa da Silva (Conference on Digital Government Research, 2025)
This study introduces a multidimensional framework designed to assess Digital Public Service Quality (PS-DigQual) within e-government systems. The proposed framework integrates three pivotal dimensions: System Quality (QSt), Operation Quality (QOp), and Information Quality (QInf). QSt ensures a robust technical foundation through infrastructure reliability, navigability, and compliance with accessibility standards. QOp focuses on responsiveness, personalization, and user support to enhance service delivery. QInf emphasizes transparency, accuracy, and the timely availability of information, thereby fostering trust and accountability. Addressing gaps in traditional models such as SERVQUAL and E-S-QUAL, the framework adapts to the unique requirements of public digital services, where transparency, inclusion, and citizen engagement are critical. The research methodology is grounded in a systematic literature review and bibliometric analysis, spanning publications from 1990 to January 2025. This approach ensures a comprehensive theoretical foundation and identifies critical gaps in existing frameworks. The study further applies the PS-DigQual framework in practical scenarios, demonstrating that improvements in one dimension positively impact others, creating a cycle of continuous enhancement. Key contributions include a scalable analytical tool for policymakers and a robust foundation for further academic inquiry. The framework’s adaptability allows it to be tailored across different cultural and institutional contexts, with the potential for incorporating emerging technologies such as artificial intelligence and blockchain. By promoting efficiency, transparency, and inclusion, PS-DigQual represents a significant advancement in evaluating and improving digital public services. The study concludes with suggestions for future research, emphasizing the development of measurement scales and strategies to ensure sustainable public value in the digital era.